2014
DOI: 10.1097/opx.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Tear Presenting in a Patient with Ectrodactyly Ectodermal Dysplasia

Abstract: In this case, the patient presented with longstanding ocular surface disease known to be associated with this patient's inherited ectoderm disorder. In addition, this patient revealed a retinal tear, raising the possibility that patients with inherited congenital ectodermal dysplasia could be at risk for damaged structures originating from the neural ectoderm. In this heterogeneous disease, we are contributing to the existing literature a case of ectodermal dysplasia syndrome with obvious ectodermal complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…ED is often accompanied by some ocular abnormalities, such as EEC syndrome (ectrodactyly, ectodermal dysplasia and cleft lip/palate syndrome, characterized by ectrodactyly, ectodermal dysplasia with severe keratitis, lacrimal duct deformities, absence of meibomian gland and blepharophimosis, and cleft lip/palate, OMIM: 129900) [8] , ankyloblepharon, ectodermal defects and cleft lip/palate (AEC) syndrome (OMIM:106260) [9] , ectodermal dysplasia, ectrodactyly, and macular dystrophy (EEM) syndrome (OMIM 225280) [10] and keratitis, ichthyosis, and deafness (KID) syndrome (OMIM 242150) [11] . It is reported that ED could be accompanied by strabismus [6] , infantile bilateral glaucoma [12] , choroideremia [13] , retinal detachment [14] , subretinal fibrosis and uveitis syndrome [15] . And these ED with ocular diseases are occasional case reports.…”
Section: Introductionmentioning
confidence: 99%
“…ED is often accompanied by some ocular abnormalities, such as EEC syndrome (ectrodactyly, ectodermal dysplasia and cleft lip/palate syndrome, characterized by ectrodactyly, ectodermal dysplasia with severe keratitis, lacrimal duct deformities, absence of meibomian gland and blepharophimosis, and cleft lip/palate, OMIM: 129900) [8] , ankyloblepharon, ectodermal defects and cleft lip/palate (AEC) syndrome (OMIM:106260) [9] , ectodermal dysplasia, ectrodactyly, and macular dystrophy (EEM) syndrome (OMIM 225280) [10] and keratitis, ichthyosis, and deafness (KID) syndrome (OMIM 242150) [11] . It is reported that ED could be accompanied by strabismus [6] , infantile bilateral glaucoma [12] , choroideremia [13] , retinal detachment [14] , subretinal fibrosis and uveitis syndrome [15] . And these ED with ocular diseases are occasional case reports.…”
Section: Introductionmentioning
confidence: 99%